Peran Guru Dalam Meningkatkan Karakter Religius Murid Di MTs Nurul Ummah - Difla Nadjih; Ahmad Nasir Ari Bowo; Salamudin Salamudin; Candra Audy; Riduan Harahap; Siti Utami; Reni Indrayani; Firman Saleh; Saidi Yako; Suhaimi Suhaimi; Sayuti Sayuti (Universitas Cokroaminoto Yogyakarta, 2020)
MTs Nurul Ummah students, among others (1) held in the morning and the reading of Asmaul Husna. (2) Dhuha prayer in congregation both students and teachers and employees. (3) Religious activities such as remembrance, istigosah, commemoration of Islamic holidays, haul, and once moved pilgrimage to Wali Sanga or scholars. The obstacle that changes the teacher in improving the religious character of MTs Nurul Ummah students is the difference in the character of students which makes it difficult for teachers to improve the religious character of students simultaneously and improve communication between teachers. The solution made by teachers in improving the religious character of MTs Nurul Ummah students is that the teachers communicate with each other by sharing, deliberation and holding meetings between teachers both with the cottage / dormitory in order to create students with religious character.